Ashṭachāpa aura Vallabha-samprādaya : eka gaveshaṇātmaka adhyayana - Gupta, Dīna Dayālu (SAMP early 20th-century Indian books project ;, 1947)
Study on the works of eight Vaishnava poets of the Vallabhachars in Hinduism.